Occurrence and molecular characterization of Aspergillus species in beach sand - Teh, L.Y.; Latiffah, Z. (Penerbit Universiti Kebangsaan Malaysia, 2015)
A total of 103 Aspergillus isolates were obtained from beach sand samples collected along Batu Ferringhi beach, Penang Island. Ten species of Aspergillus were identified and the most common species was A. tubingensis (33%) followed by A. aculeatus (21.4%), A. flavus (20.4%), A. niger (9.7%), A. terreus (6.80%), A. fumigatus (2.91%), A. ibericus (1.94%), A. sydowii (1.94%), A. carbonarius (0.98%) and A. tamarii (0.98%). Maximum likelihood tree of combined dataset of ITS regions and β-tubulin sequences showed that the same species were grouped in the same clade. The present study indicated that beach sand harbor a variety of Aspergillus species and the occurrence of Aspergillus in the sand might pose health concern in case of long term exposure as some species such as A. fumigatus, A. flavus, A. niger and A. terreus are potentially pathogenic especially to immune compromised individual. The present study also contribute to the knowledge on the diversity of Aspergillus species in the beach environment as well as contribute knowledge on the taxonomic relationship of Aspergillus species in Malaysia.